Proyecto construcción del centro materno infantil – UNSM Tomo II - Ramirez Reategui, Augusto (1998)
To determine the cost of a work by performing or simply "budget" is required to carefully observe details in the treatment of its three basic components: the mqcp, 1 as specifications and analysis of unit costs, all of which are expressed through products, items and sub - items as elements that identify the different parts of a building. These components need to be fully agreed between if and identified within a classifier which allows easy handling of file systems, whether manual or computer; requiring is also that your ordering us allows access to the greater amount of concepts within them existing in the universe of the activity construction. Gathering of the information necessary to make a proper encoding of pair you das, as well as specify each one of them, prepare their cost analysis and outlining the update system of the...